Remote Ischemic Preconditioning Has No Short Term Effect on Blood Pressure, Heart Rate, and Arterial Stiffness in Healthy Young Adults - Müller, Jan; Taebling, Marius; Oberhoffer, Renate (Frontiers in Physiology, 2019)
Objective: Remote ischemic preconditioning (RIPC) are short episodes of ischemia and reperfusion applied to remote tissue to trigger responses in a specific organ or cardiovascular bed. This study investigates whether RIPC has a short-term effect on blood pressure (BP), heart rate and arterial stiffness. Patients and Methods: From March 2018 to August 2018, we included 40 healthy volunteers (23 female, age 25.6 ± 2.8 years) into this single-blinded randomized-controlled crossover trial. After measuring BP, heart rate and arterial stiffness in supine position participants were randomized into intervention or SHAM group. The intervention group then underwent a RIPC protocol (3 cycles of 5 min of 200 mmHg ischemia followed by 5 min reperfusion) at the thigh. The SHAM group followed the same protocol just on the upper arm with 40 mmHg pressure inflation. Directly after this 30-minutes procedure a reassessment of hemodynamic measures was conducted. Results: There were no significant changes in all five outcome parameters when comparing the effect of RIPC to SHAM. In peripheral systolic BP the mean difference between groups was ∆1.14 ± 6.5 mmHg, (p=.672) and for diastolic BP ∆-0.69 ± 4.5 mmHg (p=.507). Heart rate shoed a ∆-0.8 ± 4.7 beats/min (p=.397). Regarding arterial stiffness measures, there was also no significant improvements thru RIPC. The mean difference between RIPC and SHAM for central systolic BP was ∆0.40 ± 7.2 mmHg (p=.951) and for PWV ∆0.01 ± 0.26 m/s (p=.563). Conclusions: This study could not find any short-term effects of RIPC on arterial stiffness, BP and heart rate in a RCT in young healthy adults.